Amazonian cosmopolitans : navigating a shamanic cosmos, shifting indigenous policies, and other modern projects - Oakdale, Suzanne (University of Nebraska Press, 2022)
"Amazonian Cosmopolitans focuses on the autobiographical accounts of two Brazilian Indigenous leaders, Prepori and Sabino, Kawaiwete men whose lives spanned the twentieth century, when Amazonia increasingly became the context of large-scale state projects. Both give accounts of how they worked in a range of interethnic enterprises from the 1920s to the 1960s in central Brazil. Prepori, a shaman, also gives an account of his relations with spirit beings that populate the Kawaiwete cosmos as he participated in these projects. Like other Indigenous Amazonians, Kawaiwete value engagement with outsiders, particularly for leaders and shamanic healers. These social engagements encourage a careful watching and learning of others' habits, customs, and sometimes languages, what could be called a kind of cosmopolitanism or an attitude of openness, leading to an expansion of the boundaries of community. The historical consciousness presented by these narrators centers on how transformations in social relations were experienced in bodily terms--how their bodies changed as new relationships formed. Amazonian Cosmopolitans offers Indigenous perspectives on twentieth-century Brazilian history as well as a way to reimagine lowland peoples as living within vast networks, bridging wide social and cosmological divides. "--